Do online peer reviews stimulate diners' continued log-in behavior: Investigating the role of emotions in the O2O meal delivery apps context. (May 2023) - Shah, Adnan Muhammad; Abbasi, Amir Zaib; Yan, Xiangbin
Abstract: There is growing evidence that online peer reviews posted on online-to-offline (O2O) commerce platforms are a valuable source of information stimuli in consumer purchase decision-making. The research into the impact of different factors related to environmental stimuli (online peer reviews) on consumers' continued log-in behavior is under-researched in the context of O2O meal delivery apps (MDAs). Drawing on the theoretical lens of stimulus-organism-response and pleasure-arousal-dominance (PAD) models, this study examined the role of text and pictographic online review content in evoking emotions that predict continued log-in behavior on MDAs. Using a quasi-experimental setup with 134 participants from Germany, the findings reveal that the textual content of reviews positively related to pleasure and arousal, whereas the pictographic content of reviews generated pleasure and arousal. All three emotions of PAD were found to be significant predictors of the MDAs continued log-in behavior. In addition to the main effects, the results also showed the mediating effect of pleasure and arousal on continued log-in behavior. Moreover, app familiarity was found to moderate the effect of review content on emotions, implying that consumers with high app familiarity evoke fewer diners' emotions than those with low app familiarity. In the unique Western cultural context of this MDAs setting, the findings have important theoretical and practical implications for academicians, MDAs managers and developers, and food delivery firms. Highlights: Investigating the role of online reviews on continued log-in behavior of meal delivery apps. Textual content of reviews significantly influences pleasure and dominance, which leads to continued log-in behavior. Pictographic content of reviews evokes pleasure and arousal, leading to continued log-in behavior. The role of pleasure and arousal as mediators is also confirmed. The association between online reviews and emotions is contingent upon app familiarity.